LEGAL ANALYSIS OF THE IMPLEMENTATION OF INFORMED CONSENT IN HEALTHCARE SERVICES IN BAUBAU CITY - Sulyanti Rachman; Rizki Mustika Suhartono (Law Jurnal, 2026)
Informed consent is a legal instrument designed to protect patients’ rights by ensuring they receive adequate information before medical procedures are performed. Although it is regulated by various laws and regulations, its implementation in healthcare practice is still often viewed merely as the fulfillment of an administrative obligation. This situation raises questions about the extent to which informed consent has fulfilled its legal purpose of ensuring the protection of patients’ rights. This study aims to analyze the implementation of informed consent in medical procedures at healthcare facilities in Baubau City from the perspective of substantive legal compliance. The study employs a normative-empirical legal method with an evidence-based regulation approach. Data were collected through literature review, interviews with medical staff, healthcare facility management, and patients, and analyzed qualitatively by comparing legal norms with implementation practices. The results indicate that the implementation of informed consent has proceeded according to procedure through the provision of information and the signing of consent forms prior to medical procedures. However, its effectiveness still faces various challenges, including limited service time, the use of medical terminology that is difficult to understand, and suboptimal mechanisms to ensure patients’ comprehension of the information provided. This study concludes that the implementation of informed consent in Baubau City has met the procedural compliance dimension but has not fully met the substantive legal compliance dimension. Therefore, strengthening medical communication and evaluating patient understanding are necessary to enhance the effectiveness of protecting patients.